Negative plate and lithium ion battery

By setting the conductive layer in the negative electrode sheet of the lithium-ion battery, the design of the conductive layer containing ferroelectric material to adsorb lithium ions, the problem of insufficient lithium embeddedness in the negative electrode in the prior art is solved, the kinetic performance and high temperature safety and stability are improved, and the Safety risks of lithium precipitation.

CN119181761APending Publication Date: 2024-12-24SHENZHEN HIGHPOWER TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411185255.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-27
Publication Date
2024-12-24

AI Technical Summary

Technical Problem

The prior art is difficult to improve the lithium embedded capacity of the negative electrode without affecting the original safety performance and energy density of lithium-ion batteries, especially at low temperatures, which lead to safety problems of lithium precipitation.

Method used

A conductive layer is arranged between the current collector and the active material layer of the negative electrode sheet. The conductive layer contains ferroelectric materials, such as perovskite structural oxides, which are used to adsorb lithium ions, reduce the movement distance of lithium ions, and improve the lithium embedded capacity and dynamics. performance.

Benefits of technology

Without affecting the battery energy density, the lithium embedded capacity and high-temperature safety and stability of the negative electrode are improved, the proportion of short-chain lipids is reduced, and the safety performance of lithium-ion batteries is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119181761A_ABST
    Figure CN119181761A_ABST
Patent Text Reader

Abstract

The invention discloses a negative plate and a lithium ion battery, the negative plate comprises a current collector, an active material layer and a conductive layer, the active material layer is coated on at least one surface of the current collector, and the conductive layer is arranged between the current collector and the active material layer; the conductive layer comprises a conductive material and a ferroelectric material, and the ferroelectric material is used for adsorbing lithium ions. When the negative plate is applied to the lithium ion battery, the conductive layer is arranged between the current collector and the active substance layer, and the ferroelectric material in the conductive layer has ferroelectric characteristics and can naturally adsorb lithium ions, so that a part of lithium ions are enriched around the conductive layer, namely, enter internal gaps of the active substance layer, and the lithium ion battery is more uniform. And the part of lithium ions can be embedded into the active substance close to the current collector during charging, so that the lithium embedding capacity of the negative electrode can be improved without influencing the original performance of the lithium ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of lithium-ion batteries, and more particularly to a negative electrode and a lithium-ion battery. Background Technology

[0002] Without breakthrough materials, the energy density of lithium batteries is unlikely to increase significantly, causing them to lag behind the evolving demands of mobile phones and new energy vehicles, leading to the development of fast charging. However, excessively fast charging at low temperatures can cause the demand for lithium intercalation in the negative electrode to exceed its intercalation capacity, potentially resulting in lithium deposition and safety issues.

[0003] To address the aforementioned issues, existing technologies typically employ either increasing the amount of short-chain lipids in the electrolyte or reducing the compaction density of the negative electrode. Increasing the amount of short-chain lipids in the electrolyte can improve the kinetic performance of lithium-ion batteries; however, these short-chain lipids have poor high-temperature stability, affecting safety performance under high-temperature conditions. Reducing the compaction density of the negative electrode can increase the negative electrode porosity and improve lithium intercalation capability, but this reduces the battery's energy density. Therefore, existing technologies lack a solution to improve the lithium intercalation capability of the negative electrode without affecting the original safety performance and energy density of the lithium-ion battery. Summary of the Invention

[0004] This invention provides a negative electrode sheet and a lithium-ion battery to solve the problem that existing technologies struggle to improve the lithium intercalation capability of the negative electrode.

[0005] Specifically, the present invention provides a negative electrode sheet comprising a current collector, an active material layer, and a conductive layer, wherein the active material layer is coated on at least one surface of the current collector, and the conductive layer is disposed between the current collector and the active material layer; the conductive layer comprises a conductive material and a ferroelectric material, wherein the ferroelectric material is used to adsorb lithium ions.

[0006] Optionally, the ferroelectric material includes one or more of the following: perovskite structure oxides, tungsten bronze type compounds, bismuth oxide type layered structure compounds, lithium niobate, lithium tantalate, lead metaniobate, and lithium lead barium niobate.

[0007] Optionally, the ferroelectric material includes BaTiO3, CaTiO3, SrTiO3, PbTiO3, ZnTiO3, BaZrO3, PbZrO3, (Sr,Ba)TiO3, (Sr,Ba)ZrO3, (Mg,Zn)TiO3, (Sr,Pb)ZrO3, (Na 1 / 2 Bi 1 / 2 TiO3, (K 1 / 2 Bi 1 / 2 TiO3, Pb(Zn) 1 / 3 Nb 2 / 3O3, Pb(Mg) 1 / 3 Nb 2 / 3 O3, Pb(Ni) 1 / 3 Nb 2 / 3 O3, Pb(Mg) 1 / 3 Ta 2 / 3 O3, Pb(Mg) 1 / 2 W 1 / 2 O3, Pb(Co) 1 / 2 W 1 / 2 O3, Pb(Fe) 1 / 2 Nb 1 / 2 O3, Pb(Fe) 1 / 2 Ta 1 / 2 O3, Pb(Fe) 2 / 3 W 1 / 3 O3, Pb(Mn) 2 / 3 W 1 / 3 One or more of Pb(Ti,Zr)O3, Pb(Ti,Zr)O3, and Ba(Ti,Zr)O3.

[0008] Optionally, when the ferroelectric material is BaTiO3, the crystal phase of BaTiO3 does not include the cubic phase.

[0009] Optionally, the mass of the ferroelectric material is 10 to 30 parts, based on 100 parts of the mass of the conductive layer.

[0010] Optionally, the particle size of the ferroelectric material is from 50 nm to 250 nm.

[0011] Optionally, the thickness of the conductive layer is 1 μm to 2 μm.

[0012] Optionally, the conductive material includes one or more of Super P, carbon nanotubes, or carbon black.

[0013] Optionally, the conductive layer further includes an adhesive, which includes one or more of sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, styrene-butadiene rubber latex, polyacrylic acid, sodium polyacrylate, lithium polyacrylate, and sodium alginate.

[0014] The present invention also provides a lithium-ion battery comprising the negative electrode sheet described in any of the above embodiments.

[0015] The beneficial effects of this invention are as follows:

[0016] In the negative electrode sheet and lithium-ion battery provided by the present invention, a conductive layer is provided between the current collector and the active material layer. The ferroelectric material in the conductive layer has ferroelectric properties and can naturally adsorb lithium ions, so that a portion of lithium ions are enriched around the conductive layer, that is, they have entered the internal gaps of the active material layer. When charging, these lithium ions can be embedded into the active material near the current collector. Therefore, the lithium intercalation capability of the negative electrode can be improved without affecting the original performance of the lithium-ion battery.

[0017] Furthermore, due to the ferroelectric properties of ferroelectric materials, lithium ions in the electrolyte tend to accumulate around the negative electrode, reducing the distance lithium ions travel during charging and thus improving kinetic performance. This reduces the proportion of short-chain lipids, improving the high-temperature safety and stability of lithium-ion batteries while mitigating the safety risks of lithium deposition. Moreover, the use of a conductive layer is a conventional approach in existing technologies, and mixing ferroelectric materials into this conductive layer does not affect the energy density of the battery cell. Attached Figure Description

[0018] To more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings used in the description of the embodiments of the present invention will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0019] Figure 1 This is a schematic microstructure diagram of an existing negative electrode sheet;

[0020] Figure 2 This is a schematic structural diagram of a negative electrode sheet according to an embodiment of the present invention;

[0021] Figure 3 This is a schematic microstructure diagram of the negative electrode sheet according to an embodiment of the present invention.

[0022] In the figure: 110, active material layer 300, 120, current collector 200, 130, conductive layer 400;

[0023] 200, current collector; 300, active material layer; 400, conductive layer; 410, conductive material; 420, ferroelectric material. Detailed Implementation

[0024] To make the technical problems solved, the technical solutions, and the beneficial effects of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative of the invention and are not intended to limit the invention.

[0025] In the description of this invention, it should be understood that the terms "longitudinal," "radial," "length," "width," "thickness," "upper," "lower," "front," "rear," "left," "right," "vertical," "horizontal," "top," "bottom," "inner," and "outer," etc., indicating orientation or positional relationships, are based on the orientation or positional relationships shown in the accompanying drawings and are only for the convenience of describing the invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation, and therefore should not be construed as a limitation of the invention. In the description of this invention, unless otherwise stated, "a plurality of" means two or more.

[0026] In the description of this invention, it should be noted that, unless otherwise explicitly specified and limited, the terms "installation," "connection," and "linking" should be interpreted broadly. For example, they can refer to a fixed connection, a detachable connection, or an integral connection; they can refer to a mechanical connection or an electrical connection; they can refer to a direct connection or an indirect connection through an intermediate medium; and they can refer to the internal connection of two components. Those skilled in the art can understand the specific meaning of the above terms in this invention based on the specific circumstances.

[0027] Figure 1 This is a schematic structural diagram of a prior art negative electrode. The structure of the negative electrode is as follows: an active material layer 110 is coated on one surface of a current collector 120, and a conductive layer 130 is disposed between the current collector 120 and the active material layer 110. The conductive layer is only used for conducting electricity. Figure 1 As shown in Figure a, before charging, lithium ions are uniformly distributed in the electrolyte. Figure 1 As shown in Figures b and c, at the start of charging, lithium ions on the surface of the active material layer 110 are inserted into the active material of the active material layer 110. Lithium ions on the surface of the negative electrode are polarized due to concentration and voltage differences and move into the interior of the electrode. Lithium ions farther from the negative electrode move to the surface of the negative electrode, repeating the lithium insertion process. At this time, whether lithium ions move from a distance to the surface of the negative electrode or from the surface of the negative electrode to the interior of the negative electrode, they are affected by the kinetic properties of the solvent, making it most difficult for the active material near the current collector to insert lithium.

[0028] Figure 2 This is a schematic structural diagram of the negative electrode sheet according to an embodiment of the present invention, such as... Figure 2 As shown, and with reference Figure 3 This invention provides a negative electrode sheet, comprising a current collector 200, an active material layer 300, and a conductive layer 400. The active material layer 300 is coated on at least one surface of the current collector 200, and the conductive layer 400 is disposed between the current collector 200 and the active material layer 300. The conductive layer 400 comprises a conductive material 410 and a ferroelectric material 420, wherein the ferroelectric material 420 is used to adsorb lithium ions.

[0029] In the negative electrode of the present invention, since a conductive layer 400 is provided between the current collector 200 and the active material layer 300, the ferroelectric material 420 in the conductive layer 400 has ferroelectric properties and can naturally adsorb lithium ions, so that a portion of lithium ions are enriched around the conductive layer 400, that is, they have entered the internal gaps of the active material layer 300. When charging, these lithium ions can be embedded into the active material near the current collector 200, thus improving the lithium intercalation capability of the negative electrode without affecting the original performance of the lithium-ion battery.

[0030] like Figure 3 As shown, when the negative electrode sheet of the present invention is used in a lithium-ion battery, as... Figure 3 As shown in Figure d, before charging, some lithium ions are concentrated around the conductive layer 400, while the remaining lithium ions are dispersed in the electrolyte. Figure 1 As shown in Figure e, at the start of charging, lithium ions enriched around the conductive layer 400 are directly embedded into the adjacent active material (i.e., embedded in the innermost layer of the active material layer 300). Simultaneously, due to the ferroelectric properties of the ferroelectric material 420, lithium ions in the electrolyte are enriched around the negative electrode, reducing the distance lithium ions travel during charging and thus improving kinetic performance. Therefore, the proportion of short-chain lipids can be reduced, improving the high-temperature safety and stability of the lithium-ion battery while considering the safety risks of lithium deposition. Furthermore, the conductive layer 400 is a conventional design in the prior art, and mixing the ferroelectric material 420 into this conductive layer 400 does not affect the energy density of the battery cell.

[0031] In one embodiment of the present invention, the ferroelectric material 420 comprises one or more of the following: perovskite structure oxides, tungsten bronze type compounds, bismuth oxide type layered structure compounds, lithium niobate, lithium tantalate, lead metaniobate, and lithium lead barium niobate. Specifically, the ferroelectric material 420 comprises BaTiO3, CaTiO3, SrTiO3, PbTiO3, ZnTiO3, BaZrO3, PbZrO3, (Sr,Ba)TiO3, (Sr,Ba)ZrO3, (Mg,Zn)TiO3, (Sr,Pb)ZrO3, (Na 1 / 2 Bi 1 / 2 TiO3, (K 1 / 2 Bi 1 / 2 TiO3, Pb(Zn) 1 / 3 Nb 2 / 3 O3, Pb(Mg) 1 / 3 Nb 2 / 3 O3, Pb(Ni) 1 / 3 Nb 2 / 3 O3, Pb(Mg) 1 / 3 Ta 2 / 3 O3, Pb(Mg) 1 / 2 W1 / 2 O3, Pb(Co) 1 / 2W 1 / 2 O3, Pb(Fe) 1 / 2 Nb 1 / 2 O3, Pb(Fe) 1 / 2 Ta 1 / 2 O3, Pb(Fe) 2 / 3 W 1 / 3 O3, Pb(Mn) 2 / 3 W 1 / 3 One or more of Pb(Ti,Zr)O3, Pb(Ti,Zr)O3, and Ba(Ti,Zr)O3.

[0032] Furthermore, when the ferroelectric material 420 is BaTiO3, the crystal phase of BaTiO3 does not include the cubic phase. Except for cubic phases, other crystal phases of BaTiO3 all possess ferroelectric properties and can naturally adsorb lithium ions in a temperature range <130℃ (covering the normal operating range of lithium-ion batteries).

[0033] In one embodiment of the present invention, with a mass of 100 parts for the conductive layer 400, the mass of the ferroelectric material 420 is 10-30 parts. Specifically, the mass of the ferroelectric material 420 is 10 parts, 15 parts, 20 parts, 25 parts, 30 parts, or within any range of the above values. Since the ferroelectric material 420 is non-conductive, if there is too much ferroelectric material 420, it will affect the conductivity of the conductive layer 400.

[0034] In one embodiment of the present invention, the ferroelectric material 420 has a particle size of 50 to 250 nm so that it can be uniformly dispersed within the conductive layer 400. For example, the particle size of the ferroelectric material 420 is 50 nm, 80 nm, 100 nm, 130 nm, 150 nm, 180 nm, 200 nm, 220 nm, 240 nm, 250 nm, or within any range of the above values.

[0035] In one embodiment of the present invention, the thickness of the conductive layer 400 is 1 to 2 μm.

[0036] In one embodiment of the present invention, the conductive material 410 includes one or more of Super P, carbon nanotubes, or carbon black.

[0037] In one embodiment of the present invention, the morphology of the ferroelectric material 420 may be granular (blocky, spherical), needle-like, sheet-like, cocoon-like, nanotube, nanowire, nanorod, nanosphere, or fibrous, etc.

[0038] In one embodiment of the present invention, the conductive layer 400 further includes an adhesive, the adhesive comprising one or more of sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, styrene-butadiene rubber latex, polyacrylic acid, sodium polyacrylate, lithium polyacrylate, and sodium alginate.

[0039] The present invention also provides a lithium-ion battery comprising the negative electrode sheet of any of the above embodiments, to possess all the effects of a negative electrode sheet.

[0040] The present invention will be further illustrated by the following examples.

[0041] Example 1

[0042] Negative electrode: A mixture of Super P, BaTiO3, and styrene-butadiene rubber emulsion in a mass ratio of 50:20:30 is coated onto the current collector to obtain a conductive layer. The conductive layer has a thickness of 1 μm, and the ferroelectric material has a particle size of 50-150 nm.

[0043] A negative electrode slurry was prepared by mixing artificial graphite (the negative electrode active material), styrene-butadiene rubber (the second binder), and sodium carboxymethyl cellulose (the third binder) in a mass ratio of 98:2, and then adding water as a solvent. The negative electrode slurry was then coated onto a conductive layer using an extrusion coating machine, followed by baking in an oven and processing with a rolling mill to obtain the negative electrode sheet.

[0044] Positive electrode sheet: A positive electrode slurry is prepared by mixing lithium cobalt oxide (positive electrode active material), carbon black (first conductive agent), and polyvinylidene fluoride (first binder) in a mass ratio of 97:1:2, and then adding N-methylpyrrolidone (solvent) for further mixing and stirring. Lithium cobalt oxide is a commercially available material that can be used at a working voltage of 4.50V.

[0045] The above-mentioned positive electrode slurry is coated on both sides of the positive electrode current collector aluminum foil using an extrusion coating machine. After baking in an oven and processing with a rolling press, the positive electrode sheet is obtained.

[0046] The positive electrode, separator, and negative electrode prepared above are wound into a bare cell with a designed capacity of 5Ah, and then packaged with an aluminum-plastic film to produce a soft-pack cell with a capacity of 5Ah ready for electrolyte injection.

[0047] The battery cell is processed through electrolyte injection and formation to obtain a lithium-ion battery. The electrolyte contains 10% short-chain lipids by mass.

[0048] Example 2

[0049] The difference between Example 2 and Example 1 is that the mass ratio of Super P, BaTiO3, and styrene-butadiene rubber latex is 45:30:25.

[0050] Example 3

[0051] The difference between Example 3 and Example 1 is that the mass ratio of carbon nanotubes, BaTiO3, and styrene-butadiene rubber latex is 55:10:35.

[0052] Example 4

[0053] The difference between Example 4 and Example 1 is that the thickness of the conductive layer is 2 μm.

[0054] Example 5

[0055] The difference between Example 5 and Example 1 is that the particle size of the ferroelectric material is 200-250 nm.

[0056] Comparative Example 1

[0057] The difference between Comparative Example 1 and Example 1 is that the conductive layer does not contain BaTiO3.

[0058] Comparative Example 2

[0059] The difference between Comparative Example 2 and Comparative Example 1 is that the proportion of short-chain lipids in the electrolyte increased from 10% to 20%.

[0060] Performance testing

[0061] The lithium-ion batteries obtained in Examples 1-5 and Comparative Example 1 were subjected to the following tests:

[0062] 1. Cyclic performance test

[0063] (1) 25℃ Cyclic performance test: The battery was charged to 4.5V at a rate of 5C (stepped charging) and discharged to 3.0V at a rate of 0.7C at 25℃. The charge and discharge cycles were performed for 100 / 300 / 500 cycles, and the cycle capacity retention rate was recorded.

[0064] (2) 45℃ Cyclic Performance Test: The battery was charged to 4.5V at a rate of 5C (stepped charging) and discharged to 3.0V at a rate of 0.7C at 45℃. The charge-discharge cycle was performed for 100 / 200 / 400 cycles, and the cycle capacity retention rate was recorded.

[0065] 2. Safety performance test

[0066] Charge the battery cell at 0.7C to the upper limit cutoff voltage and maintain the voltage at 0.05C. At an ambient temperature of 25℃±5℃, place the fully charged sample in a thermal shock test chamber, then raise the temperature to 135℃±2℃ at a rate of 15℃±2℃ / min and maintain this temperature for 60 minutes. Observe whether the battery catches fire or explodes. If it neither catches fire nor explodes, the safety performance is indicated as "safe"; if it only catches fire, it is indicated as "fire"; if it only explodes, it is indicated as "explosion"; if it both catches fire and explodes, the safety performance is indicated as "fire and explosion". Record the results in Table 1.

[0067] Table 1

[0068]

[0069] As can be seen from the test results in Table 1, compared with Comparative Example 1, the kinetic performance of Examples 1-5 was significantly improved with the addition of BaTiO3, the room temperature cycling capacity retention rate was greatly improved, and the high temperature cycling capacity retention rate was similar.

[0070] Compared with Comparative Example 2, Examples 1, 2, and 4, with sufficient BaTiO3 and a reduced proportion of short-chain lipids, showed similar room temperature cycling capacity retention, improved high temperature cycling capacity retention, and significantly improved high temperature thermal shock safety performance, meeting the expected results.

[0071] Comparing the test results of Examples 1-3, it can be seen that under this chemical system, the performance of Super P, BaTiO3, and styrene-butadiene rubber latex in Example 1 is the best, and it is similar to that of Example 2 (BaTiO3 increased to 30), and better than that of Example 3 (BaTiO3 decreased to 10). Therefore, it can be inferred that the proportion of BaTiO3 in Example 1 already meets the kinetic requirements, while the proportion in Example 3 is insufficient.

[0072] Comparing Examples 1 and 4, the lithium-ion batteries obtained from both have similar performance, thus it can be seen that the amount of BaTiO3 contained in the 1μm conductive layer is sufficient to meet the kinetic requirements.

[0073] Compared with Example 1, when the particle size of BaTiO3 increases in Example 5, the number of particles decreases proportionally, which also reduces the improvement on kinetic performance and decreases the capacity retention rate during room temperature cycling.

[0074] The above-described embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention, and should all be included within the protection scope of the present invention.

Claims

1. A negative electrode sheet, characterized in that: It includes a current collector, an active material layer and a conductive layer, wherein the active material layer is coated on at least one surface of the current collector, and the conductive layer is arranged between the current collector and the active material layer; the conductive layer includes a conductive material and a ferroelectric material, and the ferroelectric material is used to adsorb lithium ions.

2. The negative electrode sheet according to claim 1, characterized in that: The ferroelectric materials include BaTiO3, CaTiO3, SrTiO3, PbTiO3, ZnTiO3, BaZrO3, PbZrO3, (Sr,Ba)TiO3, (Sr,Ba)ZrO3, (Mg,Zn)TiO3, (Sr,Pb)ZrO3, (Na 1 / 2 Bi 1 / 2 )TiO3、(K 1 / 2 Bi 1 / 2 )TiO3、Pb(Zn 1 / 3 Nb 2 / 3 )O3、Pb(Mg 1 / 3 Nb 2 / 3 )O3、Pb(Ni 1 / 3 Nb 2 / 3 )O3、Pb(Mg 1 / 3 Ta 2 / 3 )O3、Pb(Mg 1 / 2 W 1 / 2 )O3、Pb(Co 1 / 2 W 1 / 2 )O3、Pb(Fe 1 / 2 Nb 1 / 2 )O3、Pb(Fe 1 / 2 Ta 1 / 2 )O3、Pb(Fe 2 / 3 W 1 / 3 )O3、Pb(Mn 2 / 3 W 1 / 3 )O3, Pb(Ti,Zr)O3 and Ba(Ti,Zr)O3 or more.

3. The negative electrode sheet according to claim 1, characterized in that: When the ferroelectric material is BaTiO3, the crystal phase of the BaTiO3 does not include a cubic phase.

4. The negative electrode sheet according to claim 1, characterized in that: Based on 100 parts by weight of the conductive layer, the weight of the ferroelectric material is 10 to 30 parts by weight.

5. The negative electrode sheet according to claim 1, characterized in that: The particle size of the ferroelectric material is 50nm to 250nm.

6. The negative electrode sheet according to claim 1, characterized in that: The thickness of the conductive layer is 1 μm to 2 μm.

7. The negative electrode sheet according to claim 1, characterized in that: The conductive material includes one or more of Super P, carbon nanotubes or carbon black; And / or, the conductive layer further includes a binder, and the binder includes one or more of sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, styrene-butadiene rubber latex, polypropylene alcohol, polyacrylic acid, sodium polyacrylate, lithium polyacrylate, and sodium alginate.

8. A lithium ion battery, characterized in that: It comprises a positive electrode sheet, an electrolyte and the negative electrode sheet according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Negative plate and preparation method thereof, secondary battery and power utilization device

    CN118763173A

  • A wearable device capable of measuring exercise performance

    KR1020240002357A

  • Current collector coated with poled ferroelectric material and manufacturing method thereof, electrode and manufacturing method thereof and electrochemical device

    KR102614426B1

  • KR20240126049A